2001
DOI: 10.1348/000709901158686
|View full text |Cite
|
Sign up to set email alerts
|

Children and road safety: Increasing knowledge does not improve behaviour

Abstract: These findings highlight the need to distinguish between children's road safety knowledge and their behaviour, particularly for teachers and parents, who may mistakenly believe that children who know more will be safer on the road.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 12 publications
1
63
0
5
Order By: Relevance
“…Even if programs like Cyrus achieve their goals of communicating pedestrian safety rules, and children in good faith try to follow those rules, can they do so? In fact, there is considerable evidence that such educational approaches are ultimately not very useful, as young children have trouble translating the information conveyed into appropriate action in complex traffic environments (e.g., Ampofp-Boateng & Thomson, 1991;Thomson et al, 2005;Zeedyk et al, 2001). For example, when children apply traffic safety rules, they often do so in a fashion that may place them at risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if programs like Cyrus achieve their goals of communicating pedestrian safety rules, and children in good faith try to follow those rules, can they do so? In fact, there is considerable evidence that such educational approaches are ultimately not very useful, as young children have trouble translating the information conveyed into appropriate action in complex traffic environments (e.g., Ampofp-Boateng & Thomson, 1991;Thomson et al, 2005;Zeedyk et al, 2001). For example, when children apply traffic safety rules, they often do so in a fashion that may place them at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems plausible that children in the target age group have not developed the necessary cognitive skills to extract, retain, and apply this information (Thomson, 1997). Moreover, there is evidence that classroom training that emphasizes safety rules is a relatively ineffective method of child pedestrian training (e.g., Van Schagen & Rothengatter, 1997;Zeedyk, Wallace, Carcary, Jones, & Larter, 2001). Finally, the unstructured nature of the curriculum raises the concern that there will be considerable variability in the manner in which it is implemented, and, ultimately, its effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Yet the literature also revealed that, in the African context, road safety is more on the conceptualization level and less on the implementation level in communities and schools. It would appear that there is a need to move from conceptualization to implementation (Forjuoh, 2003;McComas et al, 2002;Odero, 2004;Ribbens, 2002;Zeedyk et al, 2001). Understanding how 10-14-year-old children conceptualize road safety education might assist in its implementation.…”
Section: Road Safety Educationmentioning
confidence: 99%
“…However, there seems to be a widespread view in the aforementioned countries that education on road safety has not achieved as much as had been hoped for and that there may even be limits to what could be achieved through education. This might shift the emphasis away from education towards engineering or urban planning measures aimed at creating an intrinsically safer environment in which the need for education might be reduced or even eliminated (Forjuoh, 2003;Muhlrad, 1998: 118-125;Ribbens, 2002;Zeedyk et al, 2001). In South Africa and other developing countries, engineering interventions are extremely expensive.…”
mentioning
confidence: 99%
“…Les travaux récents montrent que les compétences cognitives et les connaissances des règles et des dangers ne sont pas directement mises en acte par les enfants dans leurs comportements de piétons (Zeedyk, Wallace, Carcary, Jones et Larter, 2001;Granié, 2004a). Plusieurs recherches ont montré le rôle de certaines variables internes, comme les émotions (Peterson, Brazeal, Oliver et Bull, 1997;Morrongiello et Matheis, 2004;Morrongiello et Matheis, 2007) ou la recherche de sensation (Hoffrage, Weber, Hertwig et Chase, 2003;Morrongiello et Lasenby, 2006), dans la perception du risque et les comportements.…”
Section: Une Approche Déterministe Du Socialunclassified